2020
DOI: 10.1016/j.asmr.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Ultrasound in Hip Arthroscopy? A Systematic Review

Abstract: Purpose The purpose of this study is to identify and summarize the current utility of intraoperative ultrasound (US) during hip arthroscopy. Methods A systematic database query of the Cochrane Database of Systematic Reviews, the Cochrane Central Register of Controlled Trials, EMBASE, PubMed (1980 to 2019), and Ovid MEDLINE (1980 to 2019) was performed. After article identification, descriptions of the surgical procedure, use of intraoperative US, procedural complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several studies and technical articles have examined intraoperative use of US during hip arthroscopy for portal placement and for diagnoses other than FAIS. 21 , 22 , 23 , 24 , 26 Technique articles describing US-guided portal placement found it to be effective and reported low rates of chondral or labral injury; however, they did not compare US with conventional fluoroscopy. 21 , 22 , 23 , 24 In a recent cadaveric study in which portals were made by the same surgeon under US versus fluoroscopic guidance, Trasolini et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies and technical articles have examined intraoperative use of US during hip arthroscopy for portal placement and for diagnoses other than FAIS. 21 , 22 , 23 , 24 , 26 Technique articles describing US-guided portal placement found it to be effective and reported low rates of chondral or labral injury; however, they did not compare US with conventional fluoroscopy. 21 , 22 , 23 , 24 In a recent cadaveric study in which portals were made by the same surgeon under US versus fluoroscopic guidance, Trasolini et al.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 , 24 , 26 Technique articles describing US-guided portal placement found it to be effective and reported low rates of chondral or labral injury; however, they did not compare US with conventional fluoroscopy. 21 , 22 , 23 , 24 In a recent cadaveric study in which portals were made by the same surgeon under US versus fluoroscopic guidance, Trasolini et al. 25 found rates of iatrogenic injury to be significantly greater with US guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a musculoskeletal-trained radiologist for the administration and interpretation of the US may have affected our results. 28 However, the intent of this study was to assess the feasibility of a fluoroscopic-trained hip arthroscopist to incorporate US into their practice; having an musculoskeletal-trained radiologist present at every hip arthroscopy case to establish portals would not be a reasonable option. Our cadaveric model also does not account for synovitis or bleeding, which may limit US visualization during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found 5 technique articles that described the use of US for the hip intraoperatively. 28 Studies referring to hip arthroscopy for the treatment of FAIS showed arthroscopic portal placement under US guidance. 29 , 30 A clinical study demonstrated favorable complication rates for US-guided hip arthroscopy compared with a conventional fluoroscopic approach, but information regarding the external validity of this result is limited.…”
mentioning
confidence: 99%